2021
DOI: 10.1080/10095020.2021.1936656
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing-based estimation of rice yields using various models: A critical review

Abstract: Reliable estimation of region-wide rice yield is vital for food security and agricultural management. Field-scale models have increased our understanding of rice yield and its estimation under theoretical environmental conditions. However, they offer little information on spatial variability effects on farm-scale yield. Remote Sensing (RS) is a useful tool to upscale yield estimates from farm scales to regional levels. Much research used RS with rice models for reliable yield estimation. As several countries s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 184 publications
(249 reference statements)
0
13
0
Order By: Relevance
“…Methods for utilizing remote sensing in calculating rice production estimates vary. Previous research shows that mapping paddy fields can be done with the use of optical imagery, radar imagery, and a combination of radar and optical imagery [4], [5]. After knowing the area of paddy fields, production estimates can be calculated using empirical, semi-empirical, and process-based models.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for utilizing remote sensing in calculating rice production estimates vary. Previous research shows that mapping paddy fields can be done with the use of optical imagery, radar imagery, and a combination of radar and optical imagery [4], [5]. After knowing the area of paddy fields, production estimates can be calculated using empirical, semi-empirical, and process-based models.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that SIF is more sensitive to water and heat stress than greenness vegetation indices (Yoshida et al, 2015;Song et al, 2018;Liu et al, 2021). Vegetation photosynthesis is subject to stress from environmental factors in the light use efficiency (LUE) model (Monteith, 1972;Porcar-Castell et al, 2014;dela Torre et al, 2021b). Wang et al (2019) showed that SIF-derived phenology was two to four times more sensitive to climate than EVI-derived phenology.…”
Section: Introductionmentioning
confidence: 99%
“…Given these complexities, additional data such as digital elevation models (DEM) need to be used. For more precise crop yield prediction, complex crop models using additional input, e.g., canopy height from LIDAR data (manned aircraft or UAV) are required [ 19 ].…”
Section: Introductionmentioning
confidence: 99%